2023
DOI: 10.1101/2023.05.03.539278
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silicoevolution of protein binders with deep learning models for structure prediction and sequence design

Abstract: There has been considerable progress in the development of computational methods for designing protein-protein interactions, but engineering high-affinity binders without extensive screening and maturation remains challenging. Here, we test a protein design pipeline that uses iterative rounds of deep learning (DL)-based structure prediction (AlphaFold2) and sequence optimization (ProteinMPNN) to design autoinhibitory domains (AiDs) for a PD-L1 antagonist. Inspired by recent advances in therapeutic design, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…An integral part of Riff-Diff is its backbone refinement protocol, in which the diffused enzyme backbones are refined in an iterative fashion. Recent work showed that the quality of de novo backbone-side chain pairs improves when predicted structures are used for subsequent sequence design (45,46). Therefore, we implemented iterative refinement cycles into Riff-Diff during which the coordinates of idealized helical fragments of the artificial motifs were used as constraints to minimize the motif backbone RMSD.…”
Section: Riff-diff Robustly Scaffolds Catalytic Arraysmentioning
confidence: 99%
“…An integral part of Riff-Diff is its backbone refinement protocol, in which the diffused enzyme backbones are refined in an iterative fashion. Recent work showed that the quality of de novo backbone-side chain pairs improves when predicted structures are used for subsequent sequence design (45,46). Therefore, we implemented iterative refinement cycles into Riff-Diff during which the coordinates of idealized helical fragments of the artificial motifs were used as constraints to minimize the motif backbone RMSD.…”
Section: Riff-diff Robustly Scaffolds Catalytic Arraysmentioning
confidence: 99%
“…One group of such methods uses the ML predictor as a black-box oracle to evaluate existing candidates. This evaluation is then used to approximate the “fitness” of sequences, which is in turn used to navigate the sequence landscape and generate a new set of candidates using tools such as evolutionary algorithms , or simulated annealing . However, approximating complex mutational landscapes using oracles representing estimated, simplifying distributions can harm the optimization process and prevent the optimal solution from being found .…”
Section: Protein Engineering Tasks Solved By Machine Learningmentioning
confidence: 99%